Dinamika Ontologis Dalam Pelaporan Keuangan: Meninjau Ulang Dialektika Ide dan Materi dalam Ilmu Akuntansi Kontemporer - Andriani A. Zain; Tiara Abdurahman; Harun Blongkod (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This article aims to explore the philosophical foundations of accounting science through the lenses of ontology and dialectics. Within the complexity of modern business environments, accounting is often narrowly perceived as a technical recording mechanism, despite the underlying tensions between the dialectics of ideas (conceptual reasoning) and the dialectics of material reality (goal-oriented practices). This study employs a literature review method to examine the relevance of philosophical thoughts from figures such as Socrates, Plato, Hegel, Karl Popper, and Thomas Kuhn in understanding the evolution of accounting standards and practices. The discussion reveals that accounting is not merely a statistical or neutral entity, but rather a product of ongoing contradictions between regulatory compliance and managerial interests, as well as between theory and practice. A deep understanding of these dialectical dynamics is therefore essential for the development of accounting knowledge that is responsive and adaptive to social and business transformations.